1977
DOI: 10.1111/j.1365-2621.1977.tb08457.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Hydrogen Ion Binding by Cereals

Abstract: A Research Note IN VITRO HYDROGEN ION BINDING BY CEREALS ABSTRACT .The comparatively higher incidence of duodenal ulcer in therice eating belts of Eastern and Southern India than in the wheat eating population of North-West India has initiated this study of the in vitro H+ ion binding capacities of six commonly used food items, namely, bran, Bengal gram, whole wheat flour, white flour, rice and 'chira' (rice brand). Both cooked and uncooked materials caused reduction in acidity, the former, in some cases, bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Our studies on in-vitro hydrogen ion binding by different cereals have shown that cooked wholewheat flour and cooked bran have a higher hydrogen ion binding capacity than cooked rice (Jalan et al, 1977). In view of these findings, the present study was designed to investigate the gastric acid secretory response and the buffer capacity of the stomach two hours after a meal in five normal and seven duodenal ulcer subjects, to a rice-and a wheat-based meal similar to the ones consumed by the Eastern and Northern Indian people.…”
mentioning
confidence: 89%
“…Our studies on in-vitro hydrogen ion binding by different cereals have shown that cooked wholewheat flour and cooked bran have a higher hydrogen ion binding capacity than cooked rice (Jalan et al, 1977). In view of these findings, the present study was designed to investigate the gastric acid secretory response and the buffer capacity of the stomach two hours after a meal in five normal and seven duodenal ulcer subjects, to a rice-and a wheat-based meal similar to the ones consumed by the Eastern and Northern Indian people.…”
mentioning
confidence: 89%